The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1038/sj.onc.1202233
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Src in human breast tumor cell lines: elevated levels of phosphotyrosine phosphatase activity that preferentially recognizes the Src carboxy terminal negative regulatory tyrosine 530

Abstract: Elevated levels of Src kinase activity have been reported in a number of human cancers, including colon and breast cancer. We have analysed four human breast tumor cell lines that exhibit high levels of Src kinase activity, and have determined that these cell lines also exhibit a high level of a phosphotyrosine phosphatase activity that recognizes the Src carboxy-terminal PTyr530 negative regulatory site. Total Src kinase activity in these cell lines is elevated as much as 30-fold over activity in normal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 39 publications
6
86
0
Order By: Relevance
“…This approach is of particular relevance because several di erent PTPs are known to target Src for dephosphorylation and activation, and the expression pattern of these PTPs varies according to cell type. Two cell types that have been identi®ed by our laboratory as possessing elevated Src activity are human melanocytes (O'Connor et al, 1992(O'Connor et al, , 1995 and several human breast cancer cell lines (Egan et al, 1999). In both situations, we have detected elevated c-Src speci®c activity and hypophosphorylation of Tyr(527/530).…”
Section: Ptp1b and Other Ptps That Might Target C-srcsupporting
confidence: 47%
See 1 more Smart Citation
“…This approach is of particular relevance because several di erent PTPs are known to target Src for dephosphorylation and activation, and the expression pattern of these PTPs varies according to cell type. Two cell types that have been identi®ed by our laboratory as possessing elevated Src activity are human melanocytes (O'Connor et al, 1992(O'Connor et al, , 1995 and several human breast cancer cell lines (Egan et al, 1999). In both situations, we have detected elevated c-Src speci®c activity and hypophosphorylation of Tyr(527/530).…”
Section: Ptp1b and Other Ptps That Might Target C-srcsupporting
confidence: 47%
“…There is a large body of evidence that has demonstrated that Src kinase activity, and sometimes Src protein levels, are elevated in several cancers including colon and breast cancer, with a correlation often observed between increases in Src kinase activity and degree of malignancy (Bolen et al, 1987;Cartwright et al, 1989;Ottenho -Kal et al, 1992;Verbeek et al, 1996;Egan et al, 1999;Biscardi et al, 1999). As mentioned previously, Src kinase activity can be activated through a number of mechanisms including: (i) binding of Src to activated growth factor receptor tyrosine kinases; (ii) dephosphorylation of the negative regulatory Tyr(527/530) residue by a PTP; and (iii) mutation.…”
Section: Involvement Of C-src Human Cancersmentioning
confidence: 99%
“…In a pilot analysis of c-Src kinase activity in a subset of tumors analysed, we failed to observe a simple 1 : 1 correlation between RPTPa overexpression and c-Src activation (data not shown). A recent biochemical approach concluded that RPTPa is not the major Src-activating PTP in breast cancer cell lines (Egan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Increased Src activity has been found, for example, in human mammary carcinomas, colon cancer and pancreatic cancer (Jacobs and Rubsamen, 1983;Rosen et al, 1986;Ottenhoff-Kalff et al, 1992;Talamonti et al, 1993;Termuhlen et al, 1993;Maa et al, 1995;Verbeek et al, 1996;Mao et al, 1997;Egan et al, 1999;Hakak and Martin, 1999;Harris et al, 1999;Shimakage et al, 2000). The increased Src kinase activity in these tumors has been proposed to be due to tyrosine phosphatase-mediated dephosphorylation of the carboxy-terminal negative regulatory element, an increase in Src protein levels and/or altered protein stability, an increase in upstream receptor tyrosine kinase activity, or loss of key regulatory proteins (Maa et al, 1995;Mao et al, 1997;Egan et al, 1999;Hakak and Martin, 1999;Harris et al, 1999;Shimakage et al, 2000;Masaki et al, 2003). A few human colon cancers exhibit Src activating mutations (Irby et al, 1999).…”
Section: Src and Integrin In Cancermentioning
confidence: 99%